2020
DOI: 10.3390/en13164063
|View full text |Cite
|
Sign up to set email alerts
|

Computational Intelligence-Based Optimization Methods for Power Quality and Dynamic Response Enhancement of ac Microgrids

Abstract: The penetration of distributed generators (DGs) in the existing power system has brought some real challenges regarding the power quality and dynamic response of the power systems. To overcome the above-mentioned issues, the researchers around the world have tried and tested different control methods among which the computational intelligence (CI) based methods have been found as most effective in mitigating the power quality and transient response problems intuitively. The significance of the mentioned optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…In [34], it is concluded that there is no universal optimisation algorithm to be the best in solving optimisation problems. Hybrid optimisation techniques can utilize the strong advantages of each optimisation algorithm to reach an optimal solution.…”
Section: • Artificial Neural Network (Ann)mentioning
confidence: 99%
“…In [34], it is concluded that there is no universal optimisation algorithm to be the best in solving optimisation problems. Hybrid optimisation techniques can utilize the strong advantages of each optimisation algorithm to reach an optimal solution.…”
Section: • Artificial Neural Network (Ann)mentioning
confidence: 99%
“…The fitness function opted for the current study is an error integrating expression called integral time absolute error (ITAE) and is given by Equation ( 17). 33 ITAE ¼…”
Section: Optimization and Its Necessity In Proposed Control Designmentioning
confidence: 99%
“…The evolution, features and validation of these three techniques are clearly mentioned in [37][38][39]. Different optimization methods for power quality and transient stability are discussed in [40][41][42]. The optimized values of controller gains, leaky factor and the step size are determined by these techniques.…”
Section: Optimization Techniquementioning
confidence: 99%